Melting of phase change materials in horizontal annuli. (October 2021) - Azad, Mohammad; Groulx, Dominic; Donaldson, Adam
Highlights: Experimental study of the melting of n-octadecane and dodecanoic acid in a horizontal annuli. Correlations are determined to predict melt volume vs time. The progression, position and shape of solid-liquid interface during melting is provided. The results presented can go a long way in helping in the validation of PCM melting numerical models. Abstract: This paper presents experimental results on melting of n -octadecane and dodecanoic acid in horizontal annuli with center-tubes of 18-, 27-, and 36-mm diameter and outer cylinder of 127-mm diameter. The PCMs were subcooled to 2.5, 7.5, 15.0, and 22.5 °C below, and heated at 8.44, 16.4, 25.3, 33.4, and 42.2 °C above their melting temperatures. Melt volumes per unit length of the enclosures and positions of solid-liquid interfaces were obtained photographically. A generic correlation is provided to predict the melt volume of PCMs for a wide range of geometric and thermal conditions. Also, the evolution of solid-liquid interfaces with time is presented. The results show that increasing the melting temperature differential from 8.44 to 25.3 °C increases the melting rate significantly and further increase does not affect the melting rate as much. A faster melting rate is observed for a larger center tube. Subcooling of the PCMs has a greater impact on the melting rates when the PCMs are heated at a low melting temperature differential. The PCMs play a significant role on the melting rate when they are heated at a low temperature; at high melting temperature differentials, the PCMs behave similarly. In addition to providing information on melting dynamics of the PCMs in horizontal annuli, these results provide a needed source for validation for numerical models.